Study of the Potential of Kuta Mandalika Beach Geochology in Central Lombok District - Nilawati Nilawati; Olivia Oktorie (Science and Environmental Journal for Postgraduate, 2019)
This study aims to analyze the geoecological potential of the coast in Central Lombok Regency. The research method uses a survey method by determining the sample by purposive sampling. The analysis unit used is a geoecological unit that is assessed for the potential and constraints of each to develop certain tourism activities. Assessment of potential uses a SWOT analysis (Strength, Weakness, Opportunity, and Threat) to determine the development of coastal areas as opportunities for surrounding communities and sustainable maintenance of resources. The development of tourist areas is able to contribute to local revenues, open business opportunities and employment opportunities and at the same time function to maintain and preserve natural and biological wealth. classification of geoecological units in the Central Lombok coast1). Coastal alluvial geoeconomic units, 2) Valley geoecological units between hills, and 3) Geoecological units of the slopes of the denudational hills.